Recognition of spider mite infestations in jujube trees based on spectral-spatial clustering of hyperspectral images from UAVs - Wu, Yue; Li, Xican; Zhang, Qing; Zhou, Xiaozhen; Qiu, Hongbin; Wang, Panpan (Frontiers in Plant Science, 2023)
Spider mite infestations are a serious hazard for jujube trees in China. The use of remote sensing technology to evaluate the health of jujube trees in large-scale intensive agricultural production is an effective means of agricultural control. Hyperspectral remote sensing has a higher spectral resolution and richer spectral information than conventional multispectral remote sensing, which improves the detection of crop pests and diseases. We used hyperspectral remote sensing data from jujube fields infested with spider mite in Hotan Prefecture, Xinjiang to evaluate their use in monitoring this important pest. We fused spectral and spatial information from the hyperspectral images and propose a method of recognizing spider mite infestation of jujube trees. Our method is based on the construction of spectral features, the fusion of spatial information and clustering of these spectral–spatial features. We evaluated the effect of different spectral–spatial features and different clustering methods on the recognition of spider mite in jujube trees. The experimental results showed that the overall accuracy of the method for the recognition of spider mites was >93% and the overall accuracy of the band clustering–density peak clustering model for the recognition of spider mite reached 96.13%. This method can be applied to the control of jujube spider mites in agricultural production.